MAIN TECTONIC UNITS OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
In the present paper in the territory of Armenia are distinguished the following basic tectonic units from the position of plate tectonics։ 1) the Armenian folded zone as northern segment of known Peri-Gondvanian Cimmerian continent, which had been detached from Gondwanaland in Permian-Triassic in the Neo-Tethys basin initiation and the North drift by the basin widening in Mesozoic time; 2) this moving was accompanied by Paleo-Tethys oceanic crust subduction under the Hercinian base of Tran Caucasian massif that led to formation of Virahayots-Artsakh (Somkhet-Artsakh) island arc construction in a course of Jurassic-Upper Cretaceous time; 3) at the collision of Cimmerian continent with Virahayots-Artsakh island arc construction of Eurasia South Margin the obduction of a shattered and melanged material of the oceanic crust (at Aptian-Upper Coniacian time) fell down to the both sides of the suture zone forming the Amasia-Sevan-Akera and Vedi ophiolite belts. As a result the territory of Armenia had been created since Upper Coniacian time. At the same time in the South the Neo-Tethyan basin starts to narrow owing to its oceanic crust northward subduction under the Iranian margin of the Cimmerian continent. It gave rise to the Urmia-Dokhtar magmatic arc a development on the southern active margin of Iran; 4) on relation to the Urmia-Dokhtar magmatic arc the territory of present Armenia became as back-arc position on distance of 300–350 km to the North of the arc. and since Lower-Middle Eocene back arc stretching and riftogene break out of the earth's crust has taken place installing the Sevan-Shirak rift and its en-echelon continuations of Vayots Dzor-Bargushat-Megri rift. They appeared to be link in the uniform Paleogene back arc en-echelon rift system of Black Sea–Adzhar-Trialet–Shirak–Megri–Talish–Southern Caspian Sea. The Orogenesis of Caucasus started since Oligocene time owing to collision of Arabia with Iran following to closure of the Zagros oceanic pool. This closure was reasoned by the Red Sea opening; 5) in a South-North compression circumstances between Arabia and Eurasia and Anatolia westward drift the latitude stretching forces were developed in Lesser Caucasus giving rise to near-meridian tearing breaks of crust, generating Upper-Pliocene Quaternary volcanic ranges, en-echelon connected with each-other by right lateral slide-slip faults forming the uniform system of Dzavakhet-Gegham-Artsakh volcanic ranges.
Keywords: Tavro-Caucasus; tectonic zoning; paleogene rifting; collision; ophiolites